Management issues in the separation system and the ratio of authorities in the Kyrgyz Republic. Historical and legal analysis (Journal of actual problems of jurisprudence, 2019)
The article is devoted to management issues in the division system and the ratio of authoritiesin the Kyrgyz Republic. Historical and legal analysis carried out in the article emphasizes thatthe establishment of political forces between branches of government and the corresponding attempts of constitutionalconsolidating the status and powers of higher and local governments is the main taskThe implementation of which opens up opportunities for further reform of state structures.In this direction, the author has identified a number of serious contradictions, which the republic is worthovercome. One of them is a proposal for solving institutional and sectoral projects.power trouble